PREVENTIVE ANGIOPLASTY IN ACUTE MYOCARDIAL INFARCTION (Неотложная медицинская помощь)
Wald D.S., Morris J.K., Wald N.J., et al. Preventive angioplasty in myocardial infarction // N. Engl. J. Med. – 2013. – Vol. 369. – P. 1115–1123.